Time-Series Comparative Analysis of Financial Performance among Cosmetics Companies Listed on the Indonesia Stock Exchange, 2021-2024 - Amalia Tizka Zhahrina; Feriona Ayurizta Iliyas; Elisabeth Lauboling; Cholis Hidayati; Tamara Franchuk; Abdulbasit Kolapo Imam (Socio-Economic and Humanistic Aspects for Township and Industry, 2026)
Financial performance assessment is essential for evaluating whether listed firms can sustain liquidity, operational efficiency, prudent leverage, and profitability during post-pandemic market recovery. This study examines the financial performance of three cosmetics and household-product companies listed on the Indonesia Stock Exchange, namely PT Mandom Indonesia Tbk, PT Victoria Care Indonesia Tbk, and PT Kino Indonesia Tbk, over the 2021-2024 period. Using a descriptive quantitative design, the study applies financial ratio analysis and time-series comparison based on secondary data obtained from annual reports, audited financial statements, company investor-relations disclosures, and Indonesia Stock Exchange documents. The analysis covers liquidity ratios, activity ratios, solvency ratios, and profitability ratios, followed by cross-company interpretation to identify relative strengths and weaknesses. The results show that PT Mandom Indonesia Tbk has the strongest current liquidity and superior performance in selected activity ratios, particularly inventory turnover and fixed-asset turnover, but its profitability weakened sharply and turned negative in 2024. PT Victoria Care Indonesia Tbk exhibits the most stable profile, supported by relatively strong profitability, low debt exposure, and rapid receivables collection. PT Kino Indonesia Tbk records strong values in total asset turnover, interest coverage, and several profitability indicators; however, some ratio values are unusually high and should be verified against the underlying statement items before being used for investment or managerial decisions. The study contributes by showing that no single firm dominates across all dimensions; therefore, financial performance evaluation in the cosmetics industry requires integrated time-series and cross-sectional analysis rather than reliance on isolated ratios.